Causes of the right of exoneration of members - in particular in private limited companies - Sousa, Cátia Barbosa; Machado, Maria João; Fernandes, Maria Malta (Revista Jurídica Portucalense, 2018)
The articles 105 and 240 of the Commercial Companies Code (CSC) estipulate that a partner may exercise the right of exoneration whenever a law or company contract allows. The Article.240º nº 1 and 5 the CSC recognizes the parties and the possibility of indicating the statutory causes, in which provide other possibilities of the member to be separated from the company, taking into account the prohibition of the constitution of a right of arbitration. A company cannot prohibit or restrict the exercise of the right of exemption, which does not mean that the partner cannot be a private exercise of the right of exoneration for abuse of the right (art.334 ° CC), since a company of power, verify that there is legitimacy on the part of the person invoking the right and that the requirements of its exercise are fulfilled.